Public Investment in Resource-Abundant Developing Countries - Berg, Andrew (IMF Working Papers; Working Paper ;, 2012)
Natural resource revenues provide a valuable source to finance public investment in developing countries, which frequently face borrowing constraints and tax revenue mobilization problems. This paper develops a dynamic stochastic small open economy model to analyze the macroeconomic effects of investing natural resource revenues, making explicit the role of pervasive features in these countries including public investment inefficiency, absorptive capacity constraints, Dutch disease, and financing needs to sustain capital. Revenue exhaustibility raises medium-term issues of how to sustain capital built during a windfall, while revenue volatility raises short-term concerns about macroeconomic instability. Using the model, country applications show how combining public investment with a resource fund---a sustainable investing approach---can help address the macroeconomic problems associated with both exhaustibility and volatility. The applications also demonstrate how the model can be used to determine the appropriate magnitude of the investment scaling-up (accounting for the financing needs to sustain capital) and the adequate size of a stabilization fund (buffer).